Post-Intensive Care Syndrome Prevalence Six Months after Critical Covid-19: Comparison between First and Second Waves - Rapin, Amandine; Boyer, François Constant; Mourvillier, Bruno; Orsini, Guillaume Giordano; Launois, Claire; Taiar, Redha; Deslee, Gaëtan; Goury, Antoine; Carazo-Mendez, Sandy (Journal of Rehabilitation Medicine, 2022)
Objective: To explore the impact of improved intensive care for COVID-19 patients on the prevalence of post-intensive care syndrome (PICS).Design: Ambispective cohort study.Patients: Post-intensive care unit COVID-19 patients from the first and second waves of COVID-19.Methods: Patients were evaluated at 6 months after infection. PICS was defined as the presence of a 1-min sit-to-stand test (1STS) score < 2.5th percentile or a Symbol Digit Modalities Test (SDMT) below the 2 standard deviation cut-off, or a Hospital Anxiety and Depression Scale score ≥ 11.Results: A total of 60 patients were included (34 from wave 1 and 26 from wave 2). Intensive care unit management improved between waves, with shorter duration of orotracheal intubation (7 vs 23.5 days, p = 0.015) and intensive care unit stay (6 vs 9.5 days, p = 0.006) in wave 2. PICS was present in 51.5% of patients after wave 1 and 52% after wave 2 (p = 0.971). Female sex and diabetes were significantly associated with PICS by multivariate analysis.Conclusion: Approximately half of post-intensive care unit COVID-19 patients have 1 or more impairments consistent with PICS at 6 months, with an impact on quality of life and participation. Improved intensive care unit management was not associated with a decrease in the prevalence of PICS. Identification of patients at risk, particularly women and diabetic patients, is essential. Further studies of underlying mechanisms and the need for rehabilitation are essential to reduce the risk of PICS. LAY ABSTRACTCOVID-19 infection can lead to hospitalization in an intensive care unit (ICU). Some patients experience physical, mental or emotional symptoms after ICU admission, collectively termed post-intensive care syndrome (PICS). It was hypothesized that improvements in management in the ICU between the first and second waves of the COVID-19 pandemic may have had a positive impact on the prevalence of PICS. In the current study, according to the definition proposed, However, the results of this study showed that, according to the definition proposed, half of all post-ICU COVID-19 patients had PICS at 6 months after infection, with no difference between waves, despite improvements in care in the ICU. In the current study, women and patients with diabetes were most frequently affected. Improving care at the acute phase seems to be insufficient to prevent PICS post-COVID. It seems necessary to improve care programmes and follow-up after the acute phase in order to prevent and manage PICS and improve quality of life for these patients.
Keywords: COVID-19; critical care; exercise capacity; long-term consequences; physical and rehabilitation medicine